Diseño geométrico y de pavimentos de la carretera Ledoy – Bellavista - Villegas Torres, Johnny Gustavo (2010)
The present thesis work called "Design geometrical and of pavement of the road Ledoy – Bellavista", was developed at the Faculty of Civil Engineering of the National University of San Martin. The planning of the project arises from the high costs generated by the transfer of its products on a road in poor condition and a low level of life of the population of Ledoy is seen highlighting by the lack of a well unpaved cart that fluidity to the population moving to different places of the region. Through the development of this project seeks that the inhabitants of the village of Ledoy have with an efficient way that integrate it with other peoples and markets to sell their products and improve their quality of life, the reason why it is necessary to perform geometrical design of pavement that will form part of the final study for the implementation of the road Ledoy - Bellavista looking for all possible parameters and improving all risks q...